ANALYSIS OF THE IMPACT OF BANKING REFORM PROGRAMS ON THE IRAQI BANKING SYSTEM FOR THE PERIOD 2004-2024 - Shaima Khattab Obaid (Scholar Express Journals, 2025)
Iraq witnessed radical changes in multiple areas after 2003, and the banking sector was one of the sectors most affected by these changes. With the implementation of economic reform programs imposed by political and economic developments, the need to restructure the banking system increased to achieve financial stability and support sustainable economic growth. Economic reform programs in Iraq during the period from 2004 to 2024 focused on improving the performance of banks, both public and private, and enhancing their role in financing economic projects and stimulating the credit market. There was also an emphasis on developing monetary and supervisory policies to ensure monetary stability and activate the banking sector's role in financing economic development, despite the challenges these programs faced, such as security crises, oil fluctuations, and administrative corruption. This study will analyze the impact of banking reform programs on the Iraqi banking system during the period from 2004 to 2024, by examining the extent to which monetary and financial policies succeeded in improving the effectiveness of Iraqi banks, whether in the areas of digital transformation, enhancing competitiveness, or interacting with local and global economic variables. In this study, we will focus on understanding how reform programs affect financial efficiency, the transition to a market economy, and the impact of this on the stability of the banking system in Iraq and its role in promoting economic development in light of the challenges facing the banking sector
Keywords: Banking reform; Monetary stability